ANALISA YURIDIS TERHADAP PERKARA WANPRESTASI DALAM PERJANJIAN JUAL BELI RUMAH - Syah, Aden; Subekti, Subekti; Widodo, Ernu (Gapenas Publisher, 2025)
The purpose of this study is to examine and analyze the decision of the Sungguminasa District Court No. 17/Pdt.G/2007/PN. Sungguminasa District Court Decision No. 17/Pdt.G/2007/PN Sungguminasa is in accordance with the facts and applicable legal provisions, and to determine and analyze the judge's decision on breach of contract in Sungguminasa District Court Decision No. 17/Pdt.G/2007/PN Sungguminasa, which applied the principle of Audi Et Alteram Partem. This study uses a normative research type supported by normative legal entities. Therefore, this research was conducted by processing legal materials obtained from various sources and literature. The results of this study describe the judge's legal considerations regarding the decision on civil case (breach of contract) No. 17/Pdt.G/2007/PN. Sungguminasa was not in accordance with the legal facts presented in the trial because it did not assess the events that occurred in their entirety regarding the physical changes to the object of the dispute, namely from type 45 to type 90, and the price increase as evidenced by the results of the local investigation and witness testimony. Thus, these changes were not taken into consideration by the judge in making the decision, as there is no obligation for a contract or agreement to be made in writing (except in formal agreements mandated by law) because as long as the requirements for a valid contract as stipulated in Article 1320 of the Civil Code are met, the contract is valid even if it is only made verbally, but it is better if the contract is made in writing